Incentive contracts and elections for politicians with multi-task problems - Gersbach, Hans; Liessem, Verena (SSRN, 2004)
We consider a model with a politician facing a multi-task problem while in office. The reelection mechanism distorts the allocation of effort in favor of tasks whose outcomes can be measured more precisely than others. We show that a hierarchy of elections and incentive contracts can alleviate this inefficiency, although the incentive contracts need to be based on the same information available to the voters at reelection date